Development and validation of a portable device for lab-free versatile nucleic acid extraction - Anthony J. Politza; Tianyi Liu; Aneesh Kshirsagar; Ming Dong; Md. Ahasan Ahamed; Weihua Guan (BioTechniques)
Nucleic acid testing (NAT) has revolutionized diagnostics by providing precise, rapid, and scalable detection methods for diverse biological samples. These recent advancements satisfy the increasing demand for on-site diagnostics, yet sample preparation remains a significant bottleneck for achieving highly sensitive diagnostic assays. There is an unmet need for compatible, efficient, and lab-free sample preparation for point-of-care NAT. To address this, we developed a portable, lab-free, and battery-powered device for extracting nucleic acids. We explored using low centrifugal forces with existing commercial chemistry, demonstrating excellent performance. We designed and tested a battery-powered device to enable lab-free extractions, and verified reagents stored out to 6 months, suggesting exceptional deployment capabilities. We evaluated our device, comparing our results against those from a benchtop centrifuge across three types of samples: HIV RNA in buffer, HIV RNA in plasma, and SARS-CoV-2 RNA in saliva. The portable device demonstrated excellent agreement with the benchtop centrifuge, indicating high reliability. By providing an effective on-site sample preparation solution, the widespread adoption of low centrifugal extractions will improve the sensitivity and reliability of NAT and will positively impact other point-of-care technologies such as next generation sequencing (NGS), biomarker detection, and environmental monitoring.